New three-dimensional flat band candidate materials Pb2As2O7 and Pb2Sn2O7 - Izumi Hase; Yoichi Higashi; Hiroshi Eisaki; Kenji Kawashima (Scientific Reports)
Abstract Energy dispersion of electrons is the most fundamental property of the solid state physics. In models of electrons on a lattice with strong geometric frustration, the band dispersion of electrons can disappear due to the quantum destructive interference of the wavefunction. This is called a flat band, and it is known to be the stage for the emergence of various fascinating physical properties. It is a challenging task to realize this flat band in a real material. In this study, we performed first-principles calculations on two compounds, Pb $$_2$$ 2 As $$_2$$ 2 O $$_7$$ 7 and Pb $$_2$$ 2 Sn $$_2$$ 2 O $$_7$$ 7 , which are candidates to have flat bands near the Fermi level. Both compounds have electronic states close to flat bands, but the band width is significantly larger than that of Pb $$_2$$ 2 Sb $$_2$$ 2 O $$_7$$ 7 shown in previous research. Nevertheless, the density of states at the Fermi level of Pb $$_2$$ 2 As $$_2$$ 2 O $$_7$$ 7 is large enough to cause the system to undergo a ferromagnetic transition. In the case of Pb $$_2$$ 2 Sn $$_2$$ 2 O $$_7$$ 7 , pseudo-gap behavior near the Fermi level was observed. These findings underscore the importance of investigating the influence of flat bands on electronic energy dispersion, providing a crucial step toward understanding the emergence and characteristics of flat bands in novel materials.